Motion, identity and the bias toward agency - Fields, Chris (Frontiers in Human Neuroscience, 2014)
The well-documented human bias toward agency as a cause and therefore an explanation of observed events is typically attributed to evolutionary selection for a “social brain.” Based on a review of developmental and adult behavioral and neurocognitive data, it is argued that the bias toward agency is a result of the default human solution, developed during infancy, to the computational requirements of object re-identification over gaps in observation of more than a few seconds. If this model is correct, overriding the bias toward agency to construct mechanistic explanations of observed events requires structure-mapping inferences, implemented by the pre-motor action planning system, that replace agents with mechanisms as causes of unobserved changes in contextual or featural properties of objects. Experiments that would test this model are discussed.